Tumor Control and Normal Tissue Complications in High-dose-rate Brachytherapy for Cervical Cancer Patients Using Ir-192 Radioactive Source - Gurpreet Kaur; Pardeep Garg; Vinod Kumar Dangwal; Baltej Singh; Garima Gaur; Romikant Grover; Simrandeep Singh; Rachana Sharma (Journal of Medical Physics, 2024)
Introduction: The purpose of the study was to calculate, tumor control probability (TCP) and normal tissue complication probability (NTCP) in cervical cancer patients and to clinically correlate the outcomes with a follow-up period of 24 months. Materials and Methods: One hundred and fifty patients were included in the present study who received 46 Gy/23 fractions/4½ weeks of external beam radiotherapy with concurrent cisplatin chemotherapy, followed by intracavitary brachytherapy of 3 different fractionations regimens, i.e., 9.5 Gy per fraction of two fractions (50 patients in Arm1), 7.5 Gy per fraction of three fractions (50 patients in Arm2), and 6.0 Gy per fraction of four fractions (50 patients in Arm3). Results: The median TCP value for Arm1, Arm2, and Arm3 was 99.6%, 94%, and 98.1%, respectively, (P < 0.01). The median NTCP value for bladder in Arm1, Arm2, and Arm3 was 0.17%, 0.04%, and 0.07%, respectively, (P = 0.05). The median NTCP value for rectum in Arm1, Arm2, and Arm3 was 4.73%, 4.35%, and 3.17%, respectively, (P = 0.052). The overall survival (OS) of 90%, 86%, and 84% was found for Arm1, Arm2, and Arm3, respectively, at 24 months of follow-up. Conclusion: TCP, NTCP, and OS rates were found higher in Arm1 as compared to the other two arms. The complications found in all arms were less, low grade, and manageable. Hence, Arm1, i.e., 9.5 Gy per fraction of two fractions can be concluded as the optimum fractionation regime in terms of radiobiological parameters as well as overall patient comfort.